Psychometric properties and factor structure of the adapted Self‐Regulation Questionnaire assessing autonomous and controlled motivation for healthful eating among youth with type 1 diabetes and their parents. (16th May 2018) - Quick, V.; Lipsky, L. M.; Nansel, T. R.
Abstract: Background: The purpose of this cross‐sectional study was to examine the psychometric properties of 2 adapted Self‐Regulation Questionnaire (SRQ) measures assessing youth with type 1 diabetes motivation internalization for healthful eating and their parents motivation internalization for providing healthy meals for the family. Methods: External validity of the adapted SRQ was evaluated with respect to healthy eating attitudes (healthful eating self‐efficacy, barriers, and outcome expectations) assessed by questionnaire, diet quality (Healthy Eating Index‐2005 [HEI‐2005]; Nutrient‐Rich Foods Index 9.3 [NRF9.3]; Whole Plant Food Density [WPFD]) assessed by 3‐day food records, and body mass index assessed by measured height and weight in youth with type 1 diabetes ( N  = 136; age 12.3 ± 2.5 years) and their parents. Results: Exploratory factor analysis with varimax rotation yielded a 2‐factor structure with the expected autonomous and controlled motivation factors for both youth and parents. Internal consistencies of subscales were acceptable (α = .66–.84). Youth autonomous and controlled motivation were positively correlated overall ( r  = 0.30, p  < .001); however, in analyses stratified by age (<13 vs. ≥13 years), the correlation was not significant for youth ≥13 years. Autonomous motivation was significantly associated ( p  < .001) with greater self‐efficacy (youth: r  = 0.39, parent: r  = 0.36), positive outcome expectations (youth: r  = 0.30, parent: r  = 0.35), and fewer barriers to healthful eating (youth: r  = −0.36, parent: r  = −0.32). Controlled motivation was positively correlated with negative outcome expectations for parents ( r  = 0.29, p  < .01) and both positive ( r  = 0.28, p  < .01) and negative ( r  = 0.34, p  < .001) outcome expectations for youth. Autonomous motivation was positively associated ( p  < .05) with diet quality indicators for parents (NRF9.3 r  = 0.22; WPFD r  = 0.24; HEI‐2005 r  = 0.22) and youth ≥13 years (NRF9.3 r  = 0.26) but not youth < 13years. Among parents, but not youth, body mass index was associated negatively with autonomous motivation ( r  = −.33, p  < .001) and positively with controlled motivation ( r  = .27, p  < .01). Conclusions: Findings provide initial support for the SRQ in this population and suggest potential developmental differences in the role of motivation on healthful eating among children, adolescents, and adults.